Determination of Priority for Recipients of Distribution Assistance Facility IKM Business Actors (Small and Medium Industries) Using the Moora Method in Langkat District - Fatimah; Novriyenni; Kadim, Lina Arliana Nur (Yayasan Kita Menulis, 2023)
To determine priority recipients of assistance facilities for IKM business actors in Langkat Regency, the criteria used in this study are the type of production, capital requirements, sales results, number of employees, and length of business. The data used in this study comes from the Department of Trade and Industry. In this study the MOORA method was used which aims to design and build a decision support system in determining priority recipients of facilities for IKM business actors. The author wants to make this decision support system using the Visual Basic application and supported by the MySQL Database so that the results are more effective and efficient. From the 10 sample data obtained by means of prioritizing recipients of assistance facilities for IKM business actors, it can be seen that those who get rank I with the highest score i.e. 0.1133 is A06 in the name of devi.